The Pandemic Leadership Model: A Study of Medical Student Values During COVID-19 - Bernard, Alec; Ortiz, Sarah C.; Jones, Elizabeth; Heung, Michael; Guetterman, Timothy C.; Kirst, Nell (International Journal of Medical Students, 2022)
Background: Leadership training in medical school continues to grow. Little information exists to guide leadership program development. Concurrently, the COVID-19 pandemic provides a real-world crucible of leadership, allowing insight into qualities and characteristics medical students value. We aim to determine what students value in leadership during a pandemic and the implicit framework students use. Methods: We conducted a cross-sectional, qualitative study using a five-item novel survey instrument developed by a consensus group of experts from family medicine, leadership development, medical education, and survey research to elicit student perceptions of effective and ineffective leadership qualities and examples during the COVID-19 pandemic at the University of Michigan Medical School. We used thematic analysis to identify overarching themes to build a model of leadership integrated with existing theory. Results: 162 students participated across all years of medical school. We identified themes of Communication, Other-Orientation, Personal Characteristics, Decisive Action, and Use of Information. These five themes were then built into the model of Pandemic Leadership within the context of complexity leadership theory and collective leadership theory. This model represents qualities and characteristics students value in good leaders during a crisis. Conclusion: This study is unique in its focus on student perceptions of leadership qualities during a real-world laboratory for leadership. We hope that this information, along with the pandemic leadership model, can serve as the first step toward relevant leadership training programs in medical education. Leadership training programs in medical education would likely benefit from grounding in the student values identified by this study.